Joy at work : organizing your professional life - Kondo, Marie; Sonenshein, Scott (Little, Brown Spark, 2020)
"The workplace is a magnet for clutter and mess. Who hasn't felt drained by wasteful meetings, disorganized papers, endless emails, and unnecessary tasks? These are the modern-day hazards of working, and they can slowly drain the joy from work, limit our chances of career progress, and undermine our well-being. There is another way. In Joy at Work, bestselling author and Netflix star Marie Kondo and Rice University business professor Scott Sonenshein offer stories, studies, and strategies to help you eliminate clutter and make space for work that really matters. Using the world-renowned KonMari Method and cutting-edge research, Joy at Work will help you overcome the challenges of workplace mess and enjoy the productivity, success, and happiness that come with a tidy desk and mind."--Amazon.